Will they resolve their difference:- A Conflict Story - V, Padhmanabhan. (International Journal of Scientific Research and Management (IJSRM), 2017)
The case study is about a conflict situation faced by a young software programmer at aninformation technology company. The case narrates the story of that programmer who faced the brunt ofa conflict experienced by his team leader. The case provides an opportunity to look at the conflicthandling styles of two individuals when the conflict is not at a felt stage. It also provides the student tolook at the conflict at its different stages and help to analyse how the conflict evolves to its maturity